Back Cover: Assessment of Bromodomain Target Engagement by a Series of BI2536 Analogues with Miniaturized BET‐BRET (ChemMedChem 23/2016). (6th December 2016) - Koblan, Luke W.; Buckley, Dennis L.; Ott, Christopher J.; Fitzgerald, Mark E.; Ember, Stuart W. J.; Zhu, Jin‐Yi; Liu, Shuai; Roberts, Justin M.; Remillard, David; Vittori, Sarah; Zhang, Wei; Schonbrunn, Ernst; et al.
Abstract : The back cover picture shows a schematic of a bioluminescent energy transfer (BRET) system that reports on in‐cell target engagement of small molecules to the bromodomain and extra‐terminal domain (BET) family of chromatin‐regulating proteins. Shown is the rendering of a fusion of BET protein (BRD4; PDB 3MXF) to NanoLuciferase (NLuc; PDB 5IBO), together with the NLuc substrate furimazine and the BET‐specific probe JQ1 tethered to a BRET‐active fluorophore. This assay can be useful for high‐throughput assessment of the on‐target cellular engagement of BET inhibitors, and can help prioritize compounds with known polypharmacology. More information can be found in the Communication by James E. Bradner et al. on page 2575 in Issue 23, 2016 (DOI:10.1002/cmdc.201600502 ).